Nepal’s posing women guerrillas: memory, subjectivity and war-time photographs - Amrita Pritam Gogoi (European Bulletin of Himalayan Research)
Studies on female perpetrators of violence have shown how agency in their war-time participation is denied through the circulation of derogatory narratives perpetuated by a lack of visual representation. Based on ethnographic work conducted in Kathmandu and Dang in 2014, 2016 and 2019, this article analyses the gendered hopes, fears and intentions among Nepal’s Maoist women ex-combatants through their use of a set of personal photographs that survived the war and identifies subjectivities made and unmade at different phases, primarily during the war and in the post-war period. Taking photographs and then storing, sorting, showing, editing and posting them on social media constitutes mnemonic labour imbued with values. This labour allows women ex-combatants to create and to retain the means of preserving their identities, memories and narratives through controlled circulation of visual accounts of their experiences.